Study on mechanical properties of sandstone damaged by blasting load under triaxial cyclic loading and unloading - Haibo Wang; Genshuo Zhu; Ziyi Lu; Qi Zong; Hao Wang (Scientific Reports)
Abstract To investigate the changes in the strength and deformation of the blast load-damaged sandstone roof plate under cyclic loading and unloading conditions at different confining pressures, a triaxial loading device was used to carry out graded cyclic unloading tests on specimens with different degrees of damage, and the test results were summarized. The effects of blast-load-induced damage, confining pressure and loading stage on the strength, cohesion, internal friction angle, residual strain and volumetric strain were analyzed. (1) Compared with that of the undamaged specimen at a confining pressure of 0 MPa, the peak stress reductions in the vibration-damaged and blast-damaged specimens were 4.93% and 9.04%, respectively. The peak stress, cohesion and internal friction angle characteristics of the undamaged specimens under triaxial cyclic loading and unloading and conventional triaxial loading were greater than those of the vibration-damaged specimens. In addition, the corresponding parameters of the vibration-damaged specimens were greater than those of the blast-damaged specimens; thus, the damage induced by the blast load reduced the ability of the rock body to resist external loads. (2) The peak stresses of the specimens with different degrees of damage increased linearly with increasing confining pressure, and the presence of confining pressure restricted the deformation of the rock body and enhanced the ability of the specimens to resist external loads. (3) Under cyclic loading and unloading, the first cycle generated the largest residual stress variable. When the confining pressures were 0, 5, 10, 15 and 20 MPa, the levels of plastic deformation of Grade I cyclic loading and unloading specimens (the amounts of total deformation and peak strain of specimens under different numbers of loading and unloading cycles) were 4.19, 4.30, 4.75, 5.11 and 5.43%, respectively. An increase in the confining pressure enhanced the deformation and failure resistance characteristics of the specimens. (4) Compared with those under conventional triaxial loading, specimens under cyclic loading and unloading failed faster after reaching the ultimate volumetric strain, and specimens damaged by blasting were more likely to fail. During deep coal mining, the bearing capacity and deformation resistance of rock masses damaged by blasting after repeated disturbance loads were greatly reduced. Therefore, the safety and stability of the surrounding rock should be strictly monitored when applying blasting pressure relief technology to avoid safety accidents.